Cost-effectiveness of positive airway pressure modalities in obesity hypoventilation syndrome with severe obstructive sleep apnoea. Issue 6 (26th March 2020) - Masa, Juan F; Mokhlesi, Babak; Benítez, Iván; Gómez de Terreros Caro, Francisco Javier; Sánchez-Quiroga, M-Ángeles; Romero, Auxiliadora; Caballero, Candela; Alonso-Álvarez, Maria Luz; Ordax-Carbajo, Estrella; Gómez-García, Teresa; González, Mónica; López-Martín, Soledad; et al.
Abstract : Background: Obesity hypoventilation syndrome (OHS) is treated with either non-invasive ventilation (NIV) or CPAP, but there are no long-term cost-effectiveness studies comparing the two treatment modalities. Objectives: We performed a large, multicentre, randomised, open-label controlled study to determine the comparative long-term cost and effectiveness of NIV versus CPAP in patients with OHS with severe obstructive sleep apnoea (OSA) using hospitalisation days as the primary outcome measure. Methods: Hospital resource utilisation and within trial costs were evaluated against the difference in effectiveness based on the primary outcome (hospitalisation days/year, transformed and non-transformed in monetary term). Costs and effectiveness were estimated from a log-normal distribution using a Bayesian approach. A secondary analysis by adherence subgroups was performed. Results: In total, 363 patients were selected, 215 were randomised and 202 were available for the analysis. The median (IQR) follow-up was 3.01 (2.91–3.14) years for NIV group and 3.00 (2.92–3.17) years for CPAP. The mean (SD) Bayesian estimated hospital days was 2.13 (0.73) for CPAP and 1.89 (0.78) for NIV. The mean (SD) Bayesian estimated cost per patient/year in the NIV arm, excluding hospitalisation costs, was €2075.98 (91.6), which was higher than the cost in the CPAP arm of €1219.06 (52.3); mean difference €857.6 (105.5). CPAP was more cost-effective than NIV (99.5% probability) because longer hospital stay in the CPAP arm was compensated for by its lower costs. Similar findings were observed in the high and low adherence subgroups. Conclusion: CPAP is more cost-effective than NIV; therefore, CPAP should be the preferred treatment for patients with OHS with severe OSA. Trial registration number: NCT01405976